Analysis of Arabic Language Curriculum and Learning System: Instrumental Analysis - Anisa Siti Muslimah; Isop Syafei (Gunung Djati Conference Series, 2025)
A clearly designed and applicable curriculum and learning system are essential for achieving educational goals. The purpose of this study is to identify the systems and instruments contained in the national education curriculum and the learning system used in Arabic language learning. The method used in this study is a systematic literature review. Data collection for the literature review was conducted through a literature review of relevant reference sources from books and journals for analysis and classification. The results obtained from this study are the K13 Curriculum system, which includes instruments for assessing attitudes, assessing knowledge, and assessing skills to achieve curriculum components. Meanwhile, in the Independent Curriculum, the instruments used to fulfill these components are assessments, both formative, summative, and diagnostic. Furthermore, in Arabic language learning, there are three learning systems: the unitary system, the branch system, and the combined system. All three systems share the same primary goal: to be able to use language correctly as a tool for communication, both directly and indirectly, both orally and in writing.